Infeksi Virus Mosaik pada Tanaman Kedelai di Bali - PUTRA, I WAYAN WIKA CENDANA; SUDANA, I MADE; TEMAJA, I GEDE RAI MAYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.1, Januari 2018, 2018)
The Mosaic Virus Infections in Soybean Plants in Bali This study aimed to detect Soybean Mosaic Virus (SMV), Cucumber Mosaic Virus (CMV), and Potyvirus that infect soybean plants in Bali. The study was conducted from January to March 2017 located in nine observation locations of soybean crops throughout Bali. Observations were made on the symptoms found in the field and the incidence of the disease was determined by the Elisa (Enzyme Linked Immunosorbent Assay) serology test by using SMV, CMV, and Potyvirus antibodies. Field observations showed that the percentage of disease incidence with mosaic symptoms was 50%. Serologic assay results showed that in all samples tested were infected by CMV, SMV and Potyvirus and multiple infections between CMV-SMV, CMV-Potyvirus, and Potyvirus-SMV. Serological test results from the mosaic symptomatic samples showed the highest CMV infection occurred in Klungkung (60%), and the lowest were in Buleleng, Jembrana, Tabanan and Bangli respectively (30%). The highest SMV infection occurred in Denpasar (60%) and the lowest occurred in Karangasem (30%). The highest Potyvirus infection occurred in Denpasar (30%) and the lowest occurred or did not occur Potyvirus infection in Jembrana and Bangli (0.0%). Through serological tests, soybean plant samples from nine observation sites of soybean plants throughout Bali were positive against the antisera of SMV, CMV, and Potyvirus.